2003
DOI: 10.1103/physreva.67.053603
|View full text |Cite
|
Sign up to set email alerts
|

Superfluidity in the interior-gap states

Abstract: We investigate superfluidity in the interior-gap states proposed by Liu and Wilczek. At weak coupling, we find the {\em gapless} interior-gap state unstable in physically accessible regimes of the parameter space, where the superfluid density is shown to be always negative. We therefore conclude that the spatially-uniform interior-gap phase is extremely unstable unless it is fully gapped; in this case, however, the state is rather similar to conventional BCS states.Comment: To appear in Physical Review

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 10 publications
1
92
0
Order By: Relevance
“…This approach has proved to yield equivalent results as that of Ref. [13]. We then specialize to the case of equal mass fermions and evaluate the superfluid density in the relevant parameter regime for the realization of the BP1 phase.…”
Section: Superfluid Density Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has proved to yield equivalent results as that of Ref. [13]. We then specialize to the case of equal mass fermions and evaluate the superfluid density in the relevant parameter regime for the realization of the BP1 phase.…”
Section: Superfluid Density Calculationmentioning
confidence: 99%
“…The theoretical interest in pairing with mismatched Fermi surfaces has been revitalized by the proposal of breachedpairing superfluidity, with a number of exotic superfluid states being proposed or revisited. [13,14] Breached-pairing superfluid phase with two gapless Fermi surfaces (BP2), related to the unstable Sarma phase, [15] was found to be stable under the introduction of new effects, such as the mass imbalance and/or momentum-dependent pairing interaction. [16,17] Important developments in the subject are recent studies by various groups [18,19,20] investigating the Feshbach-resonant regime of strong interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Superfluidity or superconductivity with mismatched Fermi momenta also appears in other systems, e.g., electronic superconductor in a strong external magnetic field [10,11], asymmetric nuclear matter [12], and in imbalanced cold atomic systems [13,14]. It has been an unsolved old problem how a BCS superconductivity is destroyed as the mismatch is increased and what exotic phases may occur before entering the normal phase.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, there should be something missing for our understanding of the pairing breaking state if we failed to observe the (LO)FF state in the mismatch regime where the magnetic or superfluid density instability [14,27] develops. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The former exhibits a chromomagnetic instability [6,7] while the latter a superfluid density instability [8]. Recent studies have demonstrated that this type of instability is related to the local phase fluctuation of the superconducting order parameter, i.e., the Nambu-Goldstone boson fields [9,10,11,12].…”
mentioning
confidence: 99%